Implementasi Hak Upah dan Kewajiban KITAS Pesepak Bola Kewargeneraan Asing di Indonesia - adawiyah, nisa robbiatul; Jazuli, E Rakhmat (Universitas Sultan Ageng Tirtayasa, 2025)
The issue of wages and football rights is still a problem for foreign national footballers. So, the government has a role in organizing public welfare. Identification of the problem in this research is how to implement the wage rights and obligations of foreign nationality footballers as footballers in Indonesia? as well as factors that become obstacles in implementing the wage rights and obligations of foreign nationality footballers as footballers in Indonesia? The theories used are the theory of authority and the theory of law enforcement. This research uses a research method, namely the empirical juridical method. The research specifications used are analytical descriptive research. This research uses primary data sources and secondary data. The data collection technique in this research uses field research techniques, library research. Data analysis in this research used a qualitative descriptive approach. The results of the research are that the implementation of the wage rights and obligations of foreign nationality footballers as footballers in Indonesia has not gone well. Factors that become obstacles in implementing the wage rights and obligations of foreign nationality footballers as footballers in Indonesia include a lack of understanding of the rules relating to the rights and obligations that must be fulfilled, lack of socialization, factors assuming that it can be postponed or later, factors indecisiveness of the competent authority, factors can be negotiated. The conclusion based on the research is that the implementation of the wage rights and obligations of foreign nationality footballers as footballers in Indonesia has not gone well. Suggestions that can be given include first, PSSI should always coordinate with each other, both the youth and sports ministry, the employment ministry and the law and human rights ministry in organizing football in Indonesia. The two PSSIs together with football stakeholders in Indonesia must consistently implement the regulations relating to the rights and obligations of football players so that no more violations are committed.